Effects of 3‐nitrooxypropanol manure fertilizer on soil health and hydraulic properties. Issue 6 (18th October 2021) - Owens, Jennifer; Hao, Xiying; Thomas, Ben W.; Stoeckli, Jessica; Soden, Courtney; Acharya, Surya; Lupwayi, Newton
Abstract: Supplementing beef cattle with 3‐nitrooxypropanol (3‐NOP) decreases enteric methane production, but it is unknown if fertilizing soil with 3‐NOP manure influences soil health. We measured soil health indicators 2 yr after manure application to a bromegrass ( Bromus L.) and alfalfa ( Medicago sativa L.) mixed crop. Treatments were: composted conventional manure (without supplements); stockpiled conventional manure; composted manure from cattle supplemented with 3‐NOP; stockpiled 3‐NOP manure; composted manure from cattle supplemented with 3‐NOP and monensin (3‐NOP+Mon), a supplement that improves digestion; stockpiled 3‐NOP+Mon manure; inorganic fertilizer (150 kg N ha –1 and 50 kg P ha –1 ); and an unamended control. Select chemical (K +, Mg 2+, Mn +, Zn +, pH, and Olsen‐P), biological (soil organic matter, active C, respiration, and extractable protein), physical (wet aggregate stability, bulk density, total porosity, and macro‐, meso‐, and micro‐porosity), and hydraulic (saturation, field capacity, wilting point, water holding capacity, and hydraulic conductivity) variables were measured. The inclusion of monensin decreased soil Zn + concentrations by 70% in stockpiled 3‐NOP+Mon compared with stockpiled conventional manure. Active C and protein in composted conventional manure were 37 and 92% higher compared with stockpiled manure, respectively, but did not vary between 3‐NOP treatments. 3‐Nitrooxypropanol did not significantly alter other soil health indicators. Our results suggest that composted and stockpiled 3‐NOP manure can be used as a nutrient source for forage crops without requiring changes to current manure management because it has minimal influence on soil health. Core Ideas: Chemical soil health indicators were not affected by 3‐nitrooxypropanol manure. 3‐Nitrooxypropanol influenced biological indicators linked to organic matter quality. 3‐Nitrooxypropanol manure affected active carbon and protein. Physical and hydraulic properties were unaffected by 3‐nitrooxypropanol manure.